Copper fiber reinforced needle-coke/carbon composite for pantograph slide and its current-carrying wear performance. (1st May 2022) - Li, Meng; Ren, Boyong; Wu, Wei; Jiang, Ke; Zhang, Jiamin; Xu, Enze; Liu, Junwu; Zhong, Honghai; Tong, Guoqing; Jiang, Yang
Abstract: Copper fiber reinforced needle-coke/carbon (CF-NC/C) composites with different copper fiber contents have been successfully developed for urban rail pantograph slide block. The mechanical properties of needle coke samples containing 0 wt%, 4 wt%, 8 wt%, 12 wt% and 16 wt% were examined separately. It is found that the presence of needle coke with high aspect ratio, strength and electrical conductivity can greatly improves the physical properties of the pure carbon matrix. Therefore, we have obtained a novel carbon matrix composite. It is also revealed that the optimized CF-NC/C with 5 wt% copper fibers (CF-NC/C-5) composite has outstanding mechanical properties, current-carrying friction wear properties. The density, resistivity, and impact strength of the CF-NC/C-5 composite are 1.8788 g cm −3, 35.18 μ Ω·m, 0.16 J cm −2, respectively. In current-carrying friction wear tests (0 A, 5 A, 10 A and 15 A), the CF-NC/C-5 shows an optimum friction wear performance. To avoid agglomeration of copper fibers, the copper fibers are added innovatively during the rolling process and uniformly distributed in the carbon matrix under the tangential force of rolling, which exhibits an improved effect on reinforcing the NC/C composites. Our results greatly advance the development of the needle-coke/carbon composite, which makes the new CF-NC/C composite an ideal candidate for sliding plate material with excellent properties.